Hospital case volume and outcomes for proximal femoral fractures in the United States: an observational study - Metcalfe, D; Salim, A; Olufajo, O; Gabbe, B; Zogg, C; Harris, M; Perry, D; Costa, M (BMJ Publishing Group: Open Access, 2016)
Objective: To explore whether older adults with isolated hip fractures benefit from treatment in high-volume hospitals. Design: Population-based observational study. Setting: All acute hospitals in California, USA. Participants: All individuals aged >65 that underwent an operation for an isolated hip fracture in California between 2007 and 2011. Patients transferred between hospitals were excluded. Primary and secondary outcomes: Quality indicators (time to surgery) and patient outcomes (length of stay, in-hospital mortality, unplanned 30-day re-admission, and selected complications). Results: 91,401 individuals satisfied the inclusion criteria. Time to operation and length of stay were significantly prolonged in low volume hospitals, by 1.96 (95% CI 1.20-2.73) and 0.70 (0.38-1.03) days respectively. However, there were no differences in clinical outcomes, including in-hospital mortality, 30-day re-admission, and rates of pneumonia, pressure ulcers, and venous thromboembolism. Conclusion: These data suggest that there is no patient safety imperative to limit hip fracture care to high-volume hospitals.